2017
DOI: 10.1155/2017/3571419
|View full text |Cite
|
Sign up to set email alerts
|

A Geometric Derivation of the Irwin-Hall Distribution

Abstract: The Irwin-Hall distribution is the distribution of the sum of a finite number of independent identically distributed uniform random variables on the unit interval. Many applications arise since round-off errors have a transformed Irwin-Hall distribution and the distribution supplies spline approximations to normal distributions. We review some of the distribution's history. The present derivation is very transparent, since it is geometric and explicitly uses the inclusion-exclusion principle. In certain specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…We note that the distribution described in Eq. ( 26) represents a generalized form of the Irwin-Hall distribution [40,41]. Therefore, it is possible to compute the volume (F L ) exactly (see Appendix D for details).…”
Section: A Local Contact Breaking Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the distribution described in Eq. ( 26) represents a generalized form of the Irwin-Hall distribution [40,41]. Therefore, it is possible to compute the volume (F L ) exactly (see Appendix D for details).…”
Section: A Local Contact Breaking Distributionsmentioning
confidence: 99%
“…This variable has the following exact distribution[40,41] P (T ) = 1 (N − 1)! N i=1 γ i T N −1 − N s=1 (−1) s−1 N dg s (T ) dT ,(D3)…”
mentioning
confidence: 99%
“…For a geometric derivation of the above formula, see [28]. On the other hand, the characteristic function of S l−1 is given by…”
Section: Appendix Bmentioning
confidence: 99%
“…Before discussing the numerical instability that is present in the distribution function of the sum of uniform(0, θ) random variables, we must first derive that function. It can be shown that if X i iid ∼ Unif(0, 1) and we take a random sample of size n from this population, then Y = n i=1 X i ∼ Irwin-Hall(n) (Marengo et al 2017), where Y has the following density and distribution functions:…”
Section: Acknowledgmentsmentioning
confidence: 99%